Short-term stress enhances individuals' adaptive behaviors: a near-infrared spectroscopy study. Issue 8 (22nd May 2020) - Shiota, Shoichi; Nomura, Michio
Abstract : Few studies have examined the influence of short-term stress on neural networks underlying impulsivity in reward/punishment behavior. The influence of short-term stress on neural networks in a sample of female participants was investigated. Participants in the experimental group first completed a speech task intended to induce stress. Next, all participants performed a reward (R)/punishment (P) Go/NoGo task, while near-infrared spectroscopy was used to assess brain activation. Results indicated that Δdeoxy-Hb in the right ventrolateral prefrontal cortex increased in the R condition compared to the P condition. Moreover, false alarm reaction times during the R condition increased in the experimental group compared to the control group. Also, commission errors in the control group increased significantly in the R condition compared to the P condition. These results suggest that individuals make more careful and adaptive actions to obtain rewards when exposed to short-term stress. Long-term and short-term stress appear to have different influences on human reward-based decision making. In the future, fMRI can be used to precisely examine the possible impulsivity-related changes in functional connectivity caused by short-term stress.